Alloys-by-design: Application to titanium alloys for optimal superplasticity. (1st October 2019) - Alabort, E.; Barba, D.; Shagiev, M.R.; Murzinova, M.A.; Galeyev, R.M.; Valiakhmetov, O.R.; Aletdinov, A.F.; Reed, R.C.
Abstract: An alloy design approach for titanium alloys is presented. New alloys are isolated, manufactured and tested with an emphasis on the superplastic response. The superplastic effect is found to be optimal between 650 to 750 ∘ C at strain rates between 8.3×10 −2 and 8.3 × 10 −3 /s – this is a substantial improvement in terms of temperature and deformation rates over traditional titanium alloys such as Ti–6Al–4V. Elongations approaching ∼ 2000% are demonstrated. Electron backscatter diffraction studies confirm a randomisation of texture and absence of significant intragranular dislocation density, confirming superplasticity and thus grain-boundary sliding as the overarching deformation mechanism. At strain rates faster than 0.01/s, the alloys exhibit large elongations ( ∼ 200–500%) but softening is evident and lower ductility results. Our results reveal that the physical factors controlling the alloy composition/property/manufacturing interrelationship are understood and quantified. Physically-based constitutive equations are presented and used to demonstrate the practical advantages of the designed alloys. Graphical abstract: Image 1